2009
DOI: 10.1002/elps.200900015
|View full text |Cite
|
Sign up to set email alerts
|

Protein attachment onto silica surfaces – a survey of molecular fundamentals, resulting effects and novel preventive strategies in CE

Abstract: This review addresses the fundamentals governing the adsorption of individual protein molecules onto the surface of fused-silica capillaries, the protein aggregation to adsorbate clusters and their final accretion to monolayers with subsequent stratification to protein multilayers. The attention in CE protein separation has primarily been focused on (i) tuning the BGE including the buffer type, ionic strength, pH and additives, (ii) tailored post-rinse procedures to detach adhered protein residues and (iii) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
123
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(126 citation statements)
references
References 255 publications
1
123
0
Order By: Relevance
“…The outcome of these studies implies that protein adsorption conformation might be controlling the function of protein on colloid deposition. On the other hand, protein conformation was universally recognized to be influenced by its adsorption concentration (density) (Urano and Fukuzaki, 2000;Nakanishi et A , 2001;Stutz, 2009). Our recent study conducted with distinct protein adsorption concentrations showed that a single type of protein, Bovine Serum Albumin (BSA), may act either as colloid deposition site or inhibitor, depending on the adsorbed conformation (Flynn et al, 2012).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…The outcome of these studies implies that protein adsorption conformation might be controlling the function of protein on colloid deposition. On the other hand, protein conformation was universally recognized to be influenced by its adsorption concentration (density) (Urano and Fukuzaki, 2000;Nakanishi et A , 2001;Stutz, 2009). Our recent study conducted with distinct protein adsorption concentrations showed that a single type of protein, Bovine Serum Albumin (BSA), may act either as colloid deposition site or inhibitor, depending on the adsorbed conformation (Flynn et al, 2012).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…It is widely accepted that when adsorbed, BSA may first take a side-on conformation, at low adsorbed concentrations, which then change gradually to an end-on conformation, as more BSA masses adsorbed and lateral repulsion between adjacent BSA molecules became significant (Ramsden, 1995;Nakanishi et al, 2001;Stutz, 2009). In the absence of direct observation, the conformation of an adsorbed BSA could be estimated by comparing the adsorbed concentration with the limiting values proposed for a full side-on BSA layer and for a full end-on BSA layer, respectively (Revilla et al 1996;Nakanishi et al 2001;Terashima and Tsuji 2003;Tencer et al 2007;Togashi et al 2009: see Figure 4).…”
Section: Bsa Adsorption Conformationmentioning
confidence: 99%
See 1 more Smart Citation
“…First of all, the active biomolecule (protein, antibody or nucleic acid) must be immobilised onto the selected surface at the appropriate surface density while maintaining its activity. The way they are immobilised (physical adsorption Ekblad & Liedberg, 2010;Kidoaki & Matsuda, 2002;Nakanishi et al, 2001) versus covalent binding (Brady & Jordaan, 2009;Frasconi et al, 2010;Gandhiraman et al, 2009;Stutz, 2009)) and the surface substrate properties (wettability, roughness… (Gandhiraman et al, 2010a)) are, amongst others, parameters affecting biomolecule density and activity. Also, once proteins are attached to surfaces, different factors are affecting their biomolecular recogition (specific binding), i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Characterisation techniques more easily applicable to a larger range of proteins were developped by Castner's (Xia et al, 2002;Wagner et al, 2003Wagner et al, , 2004Belu et al, 2003;H. Wang et al, 2004;Cheng et al, 2006;Baugh et al, 2010;Liu et al, 2010) and Aoyagi's (Aoyagi et al, 2008a, 2008b, 2009Okada et al, 2008) groups. They successfully adapted time-of-flight secondary ion mass spectroscopy (ToF-SIMS) in order to discriminate protein orientation by precisely probing ionised fragments peaks associated to particular amino acids (by using principal component analysis).…”
Section: Introductionmentioning
confidence: 99%